Is faster better? Impact of operative time on postoperative outcomes after VATS anatomical pulmonary resection. (28th May 2021) - Forster, C; Ojanguren, A; Perentes, J Y; Zellweger, M; Krueger, T; Gonzalez, M
Abstract: Objective: Video-Assisted Thoracic Surgery (VATS) is now the preferred approach for standard anatomical pulmonary resections. However, operative time (OT) for this technique is correlated to many aspects, such as the surgical complexity or the surgeon's experience and skills. The aim of this study was to identify the factors associated with prolonged OTs and to assess the impact of OT on the development of post-operative complications after VATS anatomical pulmonary resections. Methods: Retrospective monocentric study including all consecutive patients undergoing a VATS anatomical pulmonary resection for benign or malignant lesions between January 2010 and December 2019. Postoperative outcomes were compared between short (<150 minutes) and long (≥150 minutes) OTs. A multivariate analysis was carried out to identify predictors of longer OTs and post-operative complications. Results: A total of 836 patients underwent a VATS anatomical pulmonary resection for malignant (n = 767, 91.7%) or benign (n = 69, 8.3%) lesions. Lobectomies were performed in 555 (66.4%), segmentectomies in 250 (29.9%), sleeve lobectomies in 16 (1.9%), bilobectomies in 11 (1.3%) and pneumonectomy in 4 (0.5%) patients. The conversion rate to thoracotomy was 7.7%. Of those 836 patients, 495 (59.2%) were operated within 150 minutes. During the 30-postoperative day period, the overall morbidity was significantly lower in the short OT group (29.1% vs. 40.5%; p = 0.001). Both the duration of drainage (3 vs. 4 days; p < 0.00001) and the length of hospital stay (6 vs. 7 days; p < 0.00001) were significantly reduced in the short OT group. Two predictors of long OT were identified on multivariate analysis: male sex (OR 1.41, p = 0.04) and neoadjuvant chemotherapy (OR 3.46, p = 0.003). A long OT was identified as an individual predictor of postoperative complications (OR 1.84, p < 0.0001). Conclusion: A prolonged OT is an individual risk factor for postoperative complications in patients undergoing VATS anatomical pulmonary resection.